Aplikasi Prediksi Debit Aliran Bulanan Berbasis Web menggunakan Model Regresi Linier - Ardiansah, Irfan; Putri, Selly Harnesa; Rubiyanti, Yanti; Pujianto, Totok (Unversitas Muhammadiyah Riau, 2024)
High rainfall is one of the main factors causing flooding in a Watershed. To overcome this problem, we develop internet-based applications to be a potential solution. This study aims to design a web-based application that is able to predict the monthly flow rate, as well as determine the flow rate at each measuring station in a Watershed. The method used in this study is software engineering by applying simple linear regression as a prediction method. In this case, rainfall acts as an independent variable, while flow discharges as a dependent variable. The prediction results showed that the flow rate at several stations that we coded A, B, C, D, and E were 3.37 m3/s, 4.49 m3/s, 11.96 m3/s, 19.79 m3/s, and 12.26 m3/s, respectively. These results provide an overview of the potential of water flow at various Sub-watershed points to be utilized as a data-based flood mitigation measures.